Dikotomi Ilmu, Islamisasi Sains dan Spiritualisasi Human Being dalam Pendidikan Islam - Nuryani; Dwi Noviani; Ely Syawalia (LP3M Universitas Al-Qur'an Ittifaqiah Indralaya, 2022)
The dichotomy of science as a separation between two disciplines, this eventually gave birth to educational dualism, namely religious education and general education. This dichotomous view that separates the religious sciences from the general sciences is contrary to the integralistic concept of Islamic teachings. The Islamic concept views science as a whole and universally, there is no term dichotomy or separation. Efforts made to overcome this dichotomy problem are the integration of religious sciences with general sciences known as the Islamization of science. The implications of the Islamization of Science in education can be seen from 3 aspects including; institutional aspects, curriculum aspects and educator aspects. The Islamization of science is an attempt to instill Islamic values into various fields of life, especially science, the harmony between Islam and science and the extent to which science is beneficial to Muslims. The development of science must bring grace to the universe, not only through the Islamization of science but also by spiritualizing human beings, the goal is to create educational outputs that have integrity, namely people who have an integrated view of life between God, humans and nature, between science knowledge and technology where this integration will mutually strengthen faith and piety, or between faith, science and charity.